Preparation method of injectable silk fibroin hydrogel
Patent Information
- Application Number
- CN202611217763.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-08-12
AI Technical Summary
[0004]然而,现有HRP交联可注射丝素体系在实际应用中存在难以兼顾的核心技术矛盾
[0044](1)本发明通过工艺改进实现了采用高浓度、高分子量丝素蛋白制备可注射水凝胶凝胶化的方法,且制备的再生丝素蛋白体系中交联剂可均匀分散,使最终制备的丝素水凝胶前驱体溶液无凝胶团块、无气泡、黏度可控、交联位点均匀分布,有效改善了堵针风险,保证了后续成胶的均匀性,然后利用该丝素水凝胶前驱体溶液成功制备得到了性能优异的可注射水凝胶。
Smart Images

Figure CN122745366B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer materials technology and relates to a method for preparing injectable silk fibroin hydrogel. Background Technology
[0002] Injectable hydrogels, with their clinical advantages such as minimally invasive implantation, in-situ shaping, and the ability to fill irregular defects, have shown great application potential in regenerative medicine fields such as soft tissue filling, bone defect repair, and drug / cell delivery. An ideal clinical-grade injectable hydrogel must meet the following core requirements: maintaining appropriate viscosity and being free of clumps before injection, allowing it to pass smoothly through standard clinical needles (21~27G), with a sufficient operating window and long-term storage stability, without clogging the needle; after injection, it should be able to rapidly gel in situ under mild conditions; and after gelation, it should have a uniform structure, controllable mechanical properties, and no toxic residues to meet the support or release needs of different tissue repair scenarios.
[0003] Silk fibroin (SF) is considered one of the ideal natural polymer materials for constructing injectable hydrogels due to its excellent biocompatibility, controllable degradation, and good extracellular matrix biomimetic properties. In existing technologies, the horseradish peroxidase (HRP)-mediated enzymatic cross-linking system is the mainstream method for preparing injectable silk fibroin hydrogels. This system achieves cross-linking and curing by catalyzing the oxidative coupling of tyrosine residues on the silk fibroin chain with HRP in the presence of hydrogen peroxide (H2O2) to form dityrosine bonds.
[0004] However, existing HRP-crosslinked injectable silk fibroin systems face core technical contradictions in practical applications. The first approach involves pre-mixing silk fibroin, HRP, and H2O2 at room temperature. However, this method results in an extremely rapid crosslinking reaction, with an operating window generally less than 5 minutes. This makes it highly susceptible to premature gel clumping during injection preparation or injection, leading to needle blockage and severe loss of injectability. The second approach uses a dual-syringe syringe (one syringe loaded with the silk fibroin and HRP mixture, and the other with H2O2) for immediate mixing at the injection end. While this method can address storage stability issues to some extent, it still suffers from uneven mixing, significant structural heterogeneity after gelation, and requires specialized dual-lumen injection instruments, increasing the complexity of clinical operations and hindering widespread adoption.
[0005] To address the injectability issue, current technologies generally employ strategies that reduce the concentration and molecular weight of silk fibroin (typically using low-concentration silk fibroin solutions). However, hydrogels formed after cross-linking low-concentration silk fibroin have fatal performance defects: on the one hand, their compressive modulus is low, making it difficult to meet the basic support requirements for non-load-bearing bone defect repair and soft tissue filling; on the other hand, the wet swelling rate of hydrogels in PBS generally exceeds 40%, making them prone to excessive swelling after implantation, compressing surrounding normal tissues and causing complications. For example, in Reference 1 (Effect of protein conformational transition rate in silk fibroin hydrogel on proliferation of surface-adherent cells [J]. Journal of Functional Polymers, 2024, 37(4):312-320.), 5 wt% silk fibroin HRP crosslinked hydrogel was used, but its optimal compressive strength after 1 day of incubation was 7.5 kPa and its optimal compressive modulus was 16.2 kPa; in Reference 2 (Comparison of Silk Hydrogels Prepared via Different Methods [J]. Polymers, 2023, 15(22),4419.), 5 wt.% silk fibroin HRP crosslinked hydrogel was used, but its PBS swelling rate after equilibration was greater than 60%.
[0006] Theoretically, using high-concentration, high-molecular-weight silk fibroin precursor solutions can significantly improve the mechanical properties and structural stability of the hydrogel after cross-linking. However, when the concentration of regenerated silk fibroin is ≥8 wt% and the molecular weight is ≥60 kDa, the entanglement between molecular chains becomes extremely severe, and the solution viscosity increases sharply. The optimal reaction temperature for HRP is 25~37°C. Adding HRP and H2O2 to the aforementioned high-concentration / high-molecular-weight silk fibroin solution at room temperature will instantly trigger an uncontrollable and rapid cross-linking reaction locally, generating heterogeneous gel clumps, directly causing needle blockage and completely destroying the injectability of the material. Therefore, it has long been generally believed in the industry that high-concentration / medium-high molecular weight silk fibroin solutions and injectability are inherently mutually exclusive, and it is difficult to achieve both simultaneously.
[0007] In summary, existing HRP-based injectable silk fibroin hydrogel technologies are limited by inherent defects such as short operating window, high mixing requirements, uneven gel structure, poor mechanical properties and high swelling rate due to low concentration, making it difficult to simultaneously meet the comprehensive clinical requirements for injectability, mechanical support, structural uniformity and long-term functionality.
[0008] Therefore, there is an urgent need to develop a novel method for preparing injectable silk fibroin hydrogels to solve the above-mentioned technical problems, while maintaining excellent injectability and taking into account the mechanical properties and biological functions after gelation. Summary of the Invention
[0009] The purpose of this invention is to solve the problems existing in the prior art and provide a method for preparing injectable silk fibroin hydrogel.
[0010] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0011] A method for preparing injectable silk fibroin hydrogel involves adding HRP solution to a regenerated silk fibroin protein solution and stirring until homogeneous. Then, a small amount of H2O2 solution is added dropwise. The mixture is then stirred and allowed to stand in a dark environment by alternating between shaking and standing to obtain a uniformly dispersed silk fibroin hydrogel precursor solution. Finally, the uniformly dispersed silk fibroin hydrogel precursor solution is transferred to a syringe for pre-crosslinking to obtain an injectable silk fibroin hydrogel.
[0012] Micro-dropleting refers to adding H2O2 solution dropwise at a rate of 0.1~1.0 mL / min using a micro-injection pump. This invention further achieves preliminary uniform dispersion of H2O2 by controlling the addition rate of H2O2, eliminating the nanoscale gel core formed by direct addition, thereby avoiding needle clogging.
[0013] During the preparation of the uniformly dispersed silk fibroin hydrogel precursor solution, the temperature of the mixing system was maintained in the range of 5~15℃.
[0014] The concentration of the regenerated silk fibroin solution is 8~20wt%, and the molecular weight of the regenerated silk fibroin is 60~250kDa;
[0015] The oscillation rate is 50~200 rpm;
[0016] Injectable hydrogels need to be stored at 4°C in a low-temperature, light-protected environment, which can effectively extend the operating window time; at low temperatures, the catalytic activity of HRP returns to a low level, the cross-linking reaction rate is significantly slowed down, and the viscosity of the system can remain stable within 14 days, meeting the clinical turnover and storage requirements.
[0017] When the hydrogel is injected into an in vivo environment at 37°C, the catalytic activity of HRP will rapidly return to normal levels, the cross-linking reaction rate will increase exponentially, and the system will complete the transformation from sol to gel within 1 to 5 minutes.
[0018] The gelation time of injectable silk fibroin hydrogel is 1~5 min, the compressive strength after molding is 100~450 kPa, the compressive modulus is 40~160 kPa, and the equilibrium swelling rate in PBS is 15~40%.
[0019] Existing technologies can only prepare injectable hydrogels using low-concentration, low-molecular-weight silk fibroin. However, hydrogels prepared from low-concentration, low-molecular-weight silk fibroin have extremely low mechanical strength and high swelling rates, which cannot meet the basic requirements of clinical applications such as soft tissue repair and drug sustained release. They usually need to be compounded or modified with other components to enhance mechanical strength. This invention uses high-concentration, high-molecular-weight silk fibroin to first prepare a uniformly dispersed silk fibroin hydrogel precursor solution, and then prepares an injectable silk fibroin hydrogel with a gelation time of 1-5 minutes, a compressive strength of 100-450 kPa after molding, a compressive modulus of 40-160 kPa, and an equilibrium swelling rate of 15-40% in PBS, which can maintain the stability of the morphology after swelling. High concentration significantly increases the density of cross-linking points per unit volume. High molecular weight molecular chains not only form HRP-catalyzed dityrosine covalent cross-links, but also have a large number of intermolecular physical entanglements. The dual network structure constructed by the two significantly improves the compressive strength and compressive modulus of the hydrogel. The high cross-linking density and strong molecular entanglement greatly limit the penetration of water molecules and network expansion. Therefore, the equilibrium swelling rate is reduced to 15-40% and the morphology is stable after swelling.
[0020] Excessive concentration or large molecular weight of silk fibroin leads to overly viscous gels at room temperature, making injection difficult. Furthermore, high molecular weight silk fibroin molecules are longer and more entangled, exhibiting a strong tendency for self-aggregation and readily forming gels due to temperature variations, causing the entire system to lose fluidity. To overcome the industry's common misconception that high-concentration / medium-high molecular weight silk fibroin is inherently incompatible with injectability, making it impossible to fabricate injectable hydrogels from high-concentration, high-molecular-weight silk fibroin, this invention first achieves uniform dispersion of the crosslinking agent in an 8-20 wt% high-concentration, 60-250 kDa high-molecular-weight regenerated silk fibroin system through process improvement. This prepares a silk fibroin hydrogel precursor solution free of gel clumps and bubbles, with controllable viscosity and uniformly distributed crosslinking sites, effectively reducing the risk of needle blockage and ensuring the uniformity of subsequent gelation. Then, using this silk fibroin hydrogel precursor solution, a high-performance injectable hydrogel was successfully prepared.
[0021] In existing high-concentration and high-molecular-weight silk fibroin solutions, the high density of active groups (tyrosine residues, amino groups) (along with high viscosity) leads to a sharp increase in the cross-linking reaction rate. If conventional mixing methods are used, localized gelation occurs during mixing, resulting in bubble formation. This invention controls the addition temperatures of the HRP solution, H2O2 solution, and regenerated silk fibroin solution to be 5-15°C lower than the lower limit of the effective catalytic temperature range of HRP (20°C). After mixing the components, the mixture is stirred and allowed to stand alternately in a light-protected environment to obtain a uniformly dispersed silk fibroin hydrogel precursor solution. Specifically:
[0022] The essence of adding HRP and H2O2 solutions to the regenerated silk fibroin solution is that HRP catalyzes the oxidation of tyrosine residues in the regenerated silk fibroin by H2O2, generating tyrosine free radicals, which then couple to form Tyr-Tyr covalent bonds. HRP and H2O2 solutions must be added sequentially to the regenerated silk fibroin solution. HRP solution should first be uniformly dispersed in the solution to ensure even distribution of enzyme molecules throughout the system. Then, when H2O2 solution is added, it initiates the oxidation reaction only at the catalytic sites of HRP, achieving HRP-controlled and uniform cross-linking initiation and avoiding localized gelation. If HRP and H2O2 solutions are mixed before being added to the regenerated silk fibroin solution, the mixture will rapidly generate a highly active catalytic intermediate, compound I, under substrate-free conditions. This intermediate has an extremely short half-life (< [missing information - likely a value in aqueous solution]). (10s) and has poor stability. When the premixed solution is added to a high-concentration silk fibroin solution, the locally high concentration of active intermediates will undergo explosive enzymatic cross-linking with the tyrosine residues they come into contact with before the solution can diffuse evenly. If H2O2 solution and HRP solution are added to the regenerated silk fibroin solution in sequence, H2O2 will directly oxidize the tyrosine residues of the regenerated silk fibroin without enzyme catalysis, triggering non-enzymatic random oxidation and local free radical bursts, forming local gelation. At the same time, H2O2 will rapidly self-decompose in the solution, and when HRP is added later, there will be no sufficient oxidant to start uniform cross-linking, ultimately resulting in a severely uneven cross-linking network and structural defects.
[0023] HRP exhibits high catalytic activity within its effective catalytic temperature range (20~50℃), with an optimal catalytic temperature (37℃) within this range, where catalytic activity reaches 100%. The temperature range 5~15℃ lower than the lower limit of HRP's effective catalytic temperature range is the sub-activity controllable range for HRP, namely 5~15℃. At this temperature, HRP will not be completely deactivated, achieving the effect of "active but not explosive"—neither the complete loss of activity will prevent subsequent pre-crosslinking and crosslinking from occurring, nor will excessive activity cause the pre-crosslinking rate and crosslinking rate to run out of control. This allows HRP solution and H2O2 solution to preferentially disperse in the silk fibroin solution, extending the crosslinking reaction time window and ensuring that the mixture only completes molecular-level bonding and layering, rather than instantaneously solidifying (forming a gel). If the temperature is more than 15°C lower than the lower limit of the effective catalytic temperature range of HRP, the catalytic activity of HRP will decrease significantly, and the subsequent pre-crosslinking and crosslinking reactions will almost stop, failing to form a final stable crosslinked system. Subsequent heating and molding will easily lead to scaffold collapse. Simultaneously, excessively low temperatures will cause the viscosity of the regenerated silk fibroin solution to surge further, increasing molecular diffusion resistance and making it more difficult to uniformly disperse H2O2 and the enzyme. Local molecular entanglement and concentration unevenness cannot be eliminated through diffusion. If the temperature is less than 5°C lower than the lower limit of the effective catalytic temperature range of HRP, the catalytic activity of HRP increases, entering a rapid catalytic range. The crosslinking reaction time window is shortened, making it impossible to complete the multiple oscillation-resting alternating uniform mixing process in time, resulting in localized gelation, returning to the shortcomings of existing technologies. Therefore, throughout the entire preparation process, the system temperature (5~15°C) must be maintained within a temperature range 5~15°C lower than the lower limit of the effective catalytic temperature range of HRP.
[0024] The regenerated silk fibroin solution, HRP solution, and H2O2 solution are mixed by alternating gentle oscillation and static standing. This avoids the continuous shear force generated by high-speed mechanical stirring, which exacerbates molecular chain entanglement and induces local silk fibroin aggregation. It also reduces the entrainment of air bubbles. At the same time, the uniform dispersion of H2O2 is achieved through molecular diffusion during the static standing stage.
[0025] If only gentle oscillation is performed without alternating periods of stillness, only macroscopic mixing of the liquid can be achieved, failing to eliminate microscopic local concentration gradients. H2O2 can only disperse at the macroscopic level and cannot penetrate the entangled regenerated silk fibroin molecular chains through molecular diffusion. Ultimately, this results in a situation where "it appears to be mixed to the naked eye, but the microscopic enzyme / oxidant concentration is severely excessive," still leading to localized gelation. The alternating oscillation-stillness method, however, breaks up localized reagent aggregation through short-term gentle oscillation, followed by long-term stillness to achieve uniform molecular-level diffusion of H2O2, expel microbubbles, and relax the regenerated silk fibroin molecular chains. This allows the system to undergo slow pre-crosslinking under low enzyme activity, forming a uniform, weakly crosslinked temporary framework, thereby eliminating uneven molecular chain entanglement and local concentration gradients, achieving system stability.
[0026] In addition, to avoid the generation of bubbles, when mixing by alternating between shaking and standing, it is also necessary to avoid the decomposition of H2O2 by light to produce O2.
[0027] As a preferred technical solution:
[0028] In the preparation method of injectable silk fibroin hydrogel described above, the concentration of HRP solution is 600~1000 U / mL (prepared with water), and the concentration of H2O2 solution is 32~50mmol / L (if the concentration is too low, the cross-linking density will be insufficient after the uniformly dispersed silk fibroin hydrogel precursor solution is cross-linked; if the concentration is too high, it will cause the regenerated silk fibroin molecular chains to break oxidatively).
[0029] The volume ratio of regenerated silk fibroin solution, HRP solution and H2O2 solution is 10:1.5~2.5:0.8~1.2.
[0030] When the volume ratio deviates from the above range, it will lead to over- or under-crosslinking of the uniformly dispersed silk fibroin hydrogel precursor solution after subsequent crosslinking: if the volume ratio of H2O2 solution is higher than the upper limit, it will cause a sudden increase in the local oxidant concentration of the system, triggering instantaneous local gelation and accompanied by oxidative degradation of the regenerated silk fibroin molecular chains; if the volume ratio of HRP solution is higher than the upper limit, it will lead to an excessively fast overall crosslinking rate, making it impossible to achieve uniform mixing; if the volume ratio of HRP or H2O2 solution is lower than the corresponding lower limit, it will lead to insufficient enzyme catalytic active sites or insufficient H2O2 supply, resulting in a low crosslinking density after subsequent crosslinking of the uniformly dispersed silk fibroin hydrogel precursor solution, and low material mechanical strength and structural stability.
[0031] The preparation method of injectable silk fibroin hydrogel described above, wherein the alternation of shaking and standing refers to shaking for 10-30 seconds and standing for 1-8 minutes each time, and repeating for 1-8 times.
[0032] The method for preparing injectable silk fibroin hydrogel as described above involves a uniformly dispersed silk fibroin hydrogel precursor solution with a viscosity of 100~2000 mPa·s; no visible air bubbles or gel clumps; and, under constant temperature conditions of 10℃ for 60 min, the transmitted light intensity fluctuation range of the uniformly dispersed silk fibroin hydrogel precursor solution, as detected by a multiple light scattering instrument, is -1.0~1.0%, and the stability index of the uniformly dispersed silk fibroin hydrogel precursor solution is <0.3.
[0033] The method for preparing injectable silk fibroin hydrogel as described above has a pre-crosslinking temperature that is 0-5°C higher than the lower limit of the effective catalytic temperature range of HRP, a pre-crosslinking time of 1-10 min, and a viscosity of 1200-3500 mPa·s for the injectable silk fibroin hydrogel.
[0034] The preparation method of the injectable silk fibroin hydrogel described above involves the following steps: immersing silkworm cocoons in a soap solution for degumming, washing, and drying to produce degummed silk; dissolving the degummed silk in a lithium bromide solution, dialysis for desalting, and concentrating to produce a regenerated silk fibroin solution.
[0035] In the method for preparing an injectable silk fibroin hydrogel as described above, the soap salt solution is a sodium carbonate solution or sodium bicarbonate solution with a molar concentration of 0.02~0.1 mol / L. Preferably, the concentration of the soap salt solution is controlled at 0.05 mol / L.
[0036] As described above, the preparation method of an injectable silk fibroin hydrogel involves degumming as follows: shredded silkworm cocoons are boiled in a soap salt solution. The degumming bath ratio (silkworm cocoons: soap salt solution) is 1g:50~150mL, and the degumming time is 20~60min. This process is repeated 3 times. If the degumming time is too short, the sericin residue will be >5%, and if it is too long, the molecular weight of the silk fibroin will decrease by >10%.
[0037] Washing and drying refers to rinsing the degummed silk repeatedly with deionized water 3-5 times, then placing it in an oven to dry at a temperature of 50-60℃ (too high a temperature can easily cause thermal denaturation of silk fibroin, while too low a temperature will result in insufficient drying, excessive moisture content, and will destroy the effective concentration of lithium bromide in the subsequent dissolution process), and drying time of 10-36 hours, thereby ensuring that the moisture content of the degummed silk is ≤5%;
[0038] The mass-to-volume ratio of degummed fibers to lithium bromide solution is 1:3~10; if the mass-to-volume ratio is too large, there will be excess solvent, which will aggravate hydrolysis; if the mass-to-volume ratio is too small, the viscosity of the solution will be too high, and the molecular chains will become entangled, resulting in uneven dissolution; the concentration of lithium bromide solution is 8~10M; if the concentration is <8M, the silk fibroin will not dissolve completely, and the residual solid fibers will be >10%; if the concentration is >10M, hydrolysis will be aggravated, and the molecular weight will drop to below 100kDa; the dissolution temperature is 40~80℃ (temperatures >50℃ will accelerate peptide bond hydrolysis, and if <40℃, the dissolution time needs to be extended to more than 12h), and the dissolution time is 2~12h;
[0039] Dialysis desalination refers to the process of dissolving degummed silk fibers in lithium bromide solution, pouring the resulting solution into a dialysis bag, and then placing the dialysis bag in deionized water to remove ions and small molecules. The dialysis bag has a capacity of 3500 Da (this ensures sufficient bromide ion permeation while maximizing the retention of target silk fibroin components and minimizing the loss of small molecule silk fibroin peptides; if the molecular weight cutoff is too high, some low molecular weight silk fibroin fragments will permeate, causing the overall molecular weight distribution to deviate from the target range). The dialysis time is 48-72 hours, with the deionized water replaced every 4-12 hours. Each replacement uses 50-150 times the volume of the dialysis solution to ensure that the conductivity of the solution after dialysis is <10 μS / cm. The molecular weight of the regenerated silk fibroin in the solution obtained after dialysis is 60-250 kDa.
[0040] Concentration refers to: filtering the dialysis solution through a PES aqueous filter membrane (polyethersulfone filter membrane) with a pore size of 0.45μm, transferring it to a vacuum drying oven, and concentrating it under conditions of 50~60℃ and 10~40kPa (too high a temperature will cause a decrease in molecular weight of >15%, and insufficient vacuum will extend the concentration time to more than 24h). The concentration time is 2~24h, thereby obtaining a regenerated silk fibroin solution with a molecular weight of 60~250kDa and a concentration of 8~20wt%.
[0041] The weight-average molecular weight of regenerated silk fibroin was determined by high performance liquid chromatography (HPLC) to ensure that the molecular weight of regenerated silk fibroin was stable at 60-250 kDa. The HPLC determination was performed by offline sampling and detection. Samples were taken once after dialysis and once after concentration to the target concentration to verify whether the molecular weight of the solution used for cross-linking was stable at 60-250 kDa.
[0042] Regenerated silk fibroin solution should be refrigerated at 4°C for ≤168h to avoid molecular chain aggregation at room temperature, which would lead to a broadening of the molecular weight distribution (PDI>2.0).
[0043] Beneficial effects:
[0044] (1) This invention realizes the gelation method of preparing injectable hydrogels using high concentration and high molecular weight silk fibroin through process improvement. The crosslinking agent in the prepared regenerated silk fibroin system can be uniformly dispersed, so that the final prepared silk fibroin hydrogel precursor solution is free of gel clumps and bubbles, has controllable viscosity, and uniformly distributed crosslinking sites. This effectively improves the risk of needle blockage and ensures the uniformity of subsequent gelation. Then, an injectable hydrogel with excellent performance was successfully prepared using the silk fibroin hydrogel precursor solution.
[0045] (2) By controlling the addition temperature of HRP solution, H2O2 solution and regenerated silk fibroin solution to be 5~15℃ lower than the lower limit of the effective catalytic temperature range of HRP, the components are mixed and then mixed in a light-proof environment by alternating shaking and standing, thereby obtaining a uniformly dispersed silk fibroin hydrogel precursor solution, avoiding the occurrence of local gelation and bubble generation during the mixing process.
[0046] (3) The present invention uses a gentle oscillation and static alternation method to mix the regenerated silk fibroin solution, HRP solution and H2O2 solution. This avoids the continuous shear force generated by high-speed mechanical stirring from aggravating molecular chain entanglement and inducing local silk fibroin aggregation, and also reduces the entrainment of air bubbles. At the same time, the uniform dispersion of H2O2 is achieved through molecular diffusion during the static stage. Attached Figure Description
[0047] Figure 1 The graph shows the backscattered light intensity variation data of the uniformly dispersed silk fibroin hydrogel precursor solution prepared in Example 1 of the present invention and the silk fibroin hydrogel precursor solution obtained in Comparative Example 3, measured by a multiple light scattering instrument.
[0048] Figure 2 The image shows the actual product of the injectable silk fibroin hydrogel prepared in Example 1 of this invention; in the image, a is a uniformly dispersed silk fibroin hydrogel precursor solution, b is the injectable silk fibroin hydrogel, and c is the molded injectable silk fibroin hydrogel. Detailed Implementation
[0049] The present invention will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0050] The manufacturers and brands mentioned in the following embodiments are merely examples. The core of this invention lies in the technical solution itself, and it is not intended to limit specific manufacturers or brands. Products from other manufacturers and brands that meet the technical requirements and performance indicators specified in this invention can also meet the application requirements of this invention and are all feasible choices.
[0051] The test methods for the relevant performance indicators in the following embodiments and comparative examples are as follows:
[0052] Molecular weight: Referring to the size exclusion chromatography method in Part IV of the Pharmacopoeia of the People's Republic of China (2025 edition), the sample was first filtered through a 0.22 μm aqueous filter membrane and degassed by sonication for 30 min. Then, the molecular weight of the degassed sample was determined using a high-performance liquid chromatograph (Chromai Leaps JYSB-0017). A differential refractive index detector was used during the test. The separation column was a Lotus SRT-C SEC-300, 7.8 × 300 mm, and the mobile phase A was 100 mM PBS + 20 mM Na2SO4. The column was calibrated using protein standards (10~300 kDa).
[0053] Viscosity: The viscosity was determined according to the third method of viscosity determination (rotational viscometer method) in General Chapter 0633 of Part IV of the Pharmacopoeia of the People's Republic of China (2025 Edition). The test temperature was the temperature of the mixing system during the preparation of the silk fibroin hydrogel precursor solution. A rotational viscometer was used, and an appropriate rotor and rotation speed were selected according to the viscosity range to ensure that the torque reading was between 10% and 90%.
[0054] Transmitted light intensity fluctuation range and stability index: A dynamic multiple light scattering instrument (TurbiscanLab) was used. expert The transmitted light intensity and stability index of the sample were measured. The test process was as follows: a dynamic multiple light scattering instrument was used. A special transparent glass bottle containing the sample was placed in the instrument. The instrument automatically recorded the transmitted light intensity at different height positions and calculated the stability index over the entire height range. The wavelength of the light beam was λ=880 nm, the test temperature was 10℃, and the test time was 60 min.
[0055] Gelation time: Using the inverted test tube method, take 10 mL of injectable silk fibroin hydrogel as the sample and place it in a dry and clean glass container. Then, place the test tube vertically into a 37℃ constant temperature water bath, with the liquid level 2 cm above the sample liquid level. Start timing from the moment the test tube is placed in the water bath. Every 30 seconds, slowly invert the test tube (tilt 90°) and observe whether the sample flows. When the sample does not flow within 30 seconds after inversion, the recorded time is the gelation time.
[0056] Compressive strength and compressive modulus: The injectable silk fibroin hydrogel was first gelled and molded into a sample. Then, the compressive strength and compressive modulus of the sample were measured by compression testing using an Instron 5966 electronic universal testing machine. The sensor was set to 500 N, and the beam speed was set to 1 mm / min. Cylindrical specimens with dimensions of 10 mm in diameter and 10 mm in thickness were used.
[0057] Equilibrium swelling rate in PBS: After the injectable hydrogel is completely gelled at 37°C, it is cut into cylindrical samples, the surface moisture is blotted dry with filter paper, and the initial wet weight is recorded. The samples are then immersed in phosphate-buffered saline (PBS) at 37°C. Every 24 hours, the samples are removed, the surface free moisture is blotted dry with filter paper, and the samples are weighed until the difference between two consecutive weighings is ≤0.5 mg. The equilibrium wet weight is recorded. Finally, the equilibrium swelling rate of the samples is calculated by weighing before and after immersion. The calculation formula is as follows: .
[0058] Example 1
[0059] A method for preparing an injectable silk fibroin hydrogel, comprising the following steps:
[0060] (1) Preparation of regenerated silk fibroin solution;
[0061] (1.1) First, put the shredded silkworm cocoons into a soap salt solution (sodium carbonate solution with a molar concentration of 0.02 mol / L) and boil for 20 min to degumme. Repeat the degumming process 3 times. Then, rinse the degummed silk with deionized water 3 times and dry it in an oven at 60℃ for 36 h to make degummed silk. The degumming bath ratio (silkworm cocoons: soap salt solution) is 1 g: 100 mL.
[0062] (1.2) First, the degummed fibers are dissolved in an 8M lithium bromide solution. Then, the solution obtained after dissolving the degummed fibers in the lithium bromide solution is poured into a dialysis bag. Then, the dialysis bag with a specification of 3500 Da is placed in deionized water to remove ions and small molecules. The mass-to-volume ratio of the degummed fibers to the lithium bromide solution is 1:3, the dissolution temperature is 40℃, and the dissolution time is 2h. The dialysis time is 72h, and the deionized water is replaced every 4h. The volume of deionized water replaced each time is 100 times the volume of the dialysis solution.
[0063] (1.3) After dialysis, the solution was filtered through a PES aqueous filter membrane with a pore size of 0.45 μm and then transferred to a vacuum drying oven. It was concentrated at 60 °C and 10 kPa for 2 h to obtain a regenerated silk fibroin solution.
[0064] The concentration of the regenerated silk fibroin solution was 8 wt%, and the molecular weight of the regenerated silk fibroin was 200 kDa.
[0065] (2) Prepare an HRP solution with a concentration of 600 U / mL by mixing HRP (effective catalytic temperature range lower limit is 20℃, Aladdin, biological activity: >250 U / mg) and water;
[0066] (3) Add HRP solution to regenerated silk fibroin solution and stir magnetically at 200 rpm for 2 min to achieve uniform molecular-level dispersion of HRP molecules in silk fibroin system. Then, use a micro-injection pump to add 32 mmol / L H2O2 aqueous solution at a rate of 0.5 mL / min. Then mix in a light-protected environment by alternating shaking and standing to obtain a uniformly dispersed silk fibroin hydrogel precursor solution. During the preparation process, the temperature of the mixing system is always maintained at 10℃, the volume ratio of regenerated silk fibroin solution, HRP solution and H2O2 solution is 10:2:1, the shaking rate is 150 rpm, and the alternating shaking and standing method means: shake for 30s and stand for 1 min each time, repeat 8 times.
[0067] The viscosity of the uniformly dispersed silk fibroin hydrogel precursor solution was 800 mPa·s; there were no visible bubbles or gel clumps; the transmitted light intensity of the uniformly dispersed silk fibroin hydrogel precursor solution fluctuated within the range of 0.2~0.5%, and the stability index of the uniformly dispersed silk fibroin hydrogel precursor solution was 0.2.
[0068] (4) Mix the uniformly dispersed silk fibroin hydrogel precursor solution (e.g.) Figure 2 (As shown in a) the sample was transferred into a syringe for pre-crosslinking to obtain an injectable silk fibroin hydrogel with a viscosity of 2000 mPa·s (e.g., ...). Figure 2 (as shown in b); where the pre-crosslinking temperature is 20℃ and the pre-crosslinking time is 10min.
[0069] The final injectable silk fibroin hydrogel had a gelation time of 2 minutes. After molding (the molded injectable silk fibroin hydrogel is shown in the image), the gelation time was 2 minutes. Figure 2 The compressive strength (as shown in c) is 200 kPa, the compressive modulus is 70 kPa, and the equilibrium swelling rate in PBS is 20%.
[0070] Comparative Example 1
[0071] A method for preparing a silk fibroin hydrogel is basically the same as in Example 1, except that in step (3), HRP solution and H2O2 solution are mixed first, and then the mixed solution is added to the regenerated silk fibroin solution.
[0072] Visible gel clumps were formed in the prepared silk fibroin hydrogel precursor solution. Under constant temperature of 10℃ for 60 min, the transmitted light intensity of the silk fibroin hydrogel precursor solution fluctuated within a range of -1.5~3% using a multiple light scattering instrument, and the stability index of the silk fibroin hydrogel precursor solution was 1.0.
[0073] The silk fibroin hydrogel precursor solution prepared in this comparative example contained a small amount of gel clumps, and the range of transmitted light intensity fluctuation and the stability index increased compared to Example 1. This is because after mixing HRP solution and H2O2 solution, a highly active catalytic intermediate of compound I is rapidly generated under substrate-free conditions. This intermediate has an extremely short half-life (< 10s in aqueous solution) and poor stability. When the premixed solution is added to a high-concentration silk fibroin solution, the locally high concentration of active intermediates will undergo explosive enzymatic cross-linking with the contacted tyrosine residues before uniform diffusion, forming heterogeneous gel clumps. In addition, these gel clumps with a density higher than that of the uncross-linked silk fibroin solution will undergo continuous and uneven sedimentation under gravity, resulting in a significant increase in the range of transmitted light intensity fluctuation, and the stability index, which integrates the changes in light intensity over all heights and all times, also increases significantly.
[0074] The silk fibroin hydrogel precursor solution used in step (4) was prepared in this comparative example;
[0075] Because the silk fibroin hydrogel precursor solution used contained visible gel clumps, the silk fibroin hydrogel prepared with it also caused needle blockage when used for injection. Therefore, the silk fibroin hydrogel prepared in this comparative example is not injectable.
[0076] Comparative Example 2
[0077] A method for preparing a silk fibroin hydrogel is basically the same as in Example 1, except that in step (3), H2O2 solution is first added to the regenerated silk fibroin solution, and then HRP solution is added to it.
[0078] The prepared silk fibroin hydrogel precursor solution produced visible bubbles and gel clumps. Under constant temperature of 10℃ for 60 min, the transmitted light intensity of the silk fibroin hydrogel precursor solution fluctuated within a range of -2 to 4%, and the stability index of the silk fibroin hydrogel precursor solution was 1.5.
[0079] The silk fibroin hydrogel precursor solution prepared in this comparative example has severe defects such as bubbles and gel clumps. Moreover, the range of transmitted light intensity fluctuation and the stability index are increased compared with Example 1. This is because H2O2 will oxidize and regenerate the tyrosine residues of silk fibroin protein without enzyme catalysis, triggering non-enzymatic random oxidation and local free radical bursts, forming local gels. These gel clumps with a density higher than that of the uncrosslinked silk fibroin solution will undergo continuous and uneven sedimentation under the action of gravity, resulting in a significant increase in the range of transmitted light intensity fluctuation. The stability index, which integrates the light intensity changes over the entire height and time, also increases significantly. At the same time, H2O2 will rapidly self-decompose in the solution. When HRP is added later, there is no sufficient oxidant to initiate uniform crosslinking, which ultimately leads to severe unevenness and structural defects in the crosslinked network.
[0080] The silk fibroin hydrogel precursor solution used in step (4) was prepared in this comparative example;
[0081] Because the silk fibroin hydrogel precursor solution used contained visible gel clumps, the silk fibroin hydrogel prepared with it also caused needle blockage when used for injection. Therefore, the silk fibroin hydrogel prepared in this comparative example is not injectable.
[0082] Comparative Example 3
[0083] A method for preparing a silk fibroin hydrogel is basically the same as in Example 1, except that the temperature of the mixing system is always kept at 18°C during the preparation process of step (3).
[0084] Visible bubbles and gel clumps were generated in the prepared silk fibroin hydrogel precursor solution. Under constant temperature of 10℃ for 60 min, the transmitted light intensity of the silk fibroin hydrogel precursor solution fluctuated within a range of -0.5~2% and the stability index of the silk fibroin hydrogel precursor solution was 0.7.
[0085] The silk fibroin hydrogel precursor solution prepared in this comparative example exhibits localized gelation and bubble defects, and the range of transmitted light intensity fluctuation and stability index are increased compared to Example 1. This is because during the preparation process in step (3) of this comparative example, the temperature of the mixing system is always 5°C lower than the lower limit of the effective catalytic temperature range of HRP, which results in the catalytic activity of HRP being higher than the low-activity state in the temperature range of this invention. At this time, the addition of H2O2 will instantly initiate a rapid cross-linking reaction, instantly forming dense gel agglomerates; in addition, these gel agglomerates with a density higher than that of the uncross-linked silk fibroin solution will undergo continuous and uneven sedimentation under the action of gravity, resulting in a significant increase in the range of transmitted light intensity fluctuation, and the stability index, which integrates the changes in light intensity over the entire height and time, also increases significantly.
[0086] The uniformly dispersed silk fibroin hydrogel precursor solution prepared in Example 1 and the silk fibroin hydrogel precursor solution obtained in Comparative Example 3 were tested for changes in backscattered light intensity using a multiple light scattering instrument. The measured data are as follows: Figure 1As shown in the figure, the transmitted light intensity variation curves of Example 1 almost completely overlap across the entire height range (0~12000μm), with minimal fluctuations, remaining stable between 0.2% and 0.5%, without obvious peaks or troughs. This indicates that the silk fibroin molecule concentration in the uniformly dispersed silk fibroin hydrogel precursor solution prepared in Example 1 is highly uniform, with no local aggregation, sedimentation, flotation, or phase separation, and the system exhibits excellent stability within a 60-minute test cycle. In contrast, the transmitted light intensity variation curves of Comparative Example 3 show a clear asymmetric trend of "high at the bottom and low at the top": the transmitted light intensity variation at the bottom (0μm) reaches a maximum of +2.0%, while at the top (12000μm) it drops to -0.5%, with significant fluctuations in the middle region; and the scan curves at different times show obvious separation, with the curve band width significantly greater than that of Example 1. This indicates that the system of Comparative Example 3 contains a large number of gel clumps, and severe phase separation has occurred, which continues to intensify over time, resulting in extremely poor system stability.
[0087] The silk fibroin hydrogel precursor solution used in step (4) was prepared in this comparative example;
[0088] Because the silk fibroin hydrogel precursor solution used contained visible gel clumps, the silk fibroin hydrogel prepared with it also caused needle blockage when used for injection. Therefore, the silk fibroin hydrogel prepared in this comparative example is not injectable.
[0089] Comparative Example 4
[0090] A method for preparing a silk fibroin hydrogel is basically the same as in Example 1, except that the temperature of the mixing system is always kept at 3°C during the preparation process of step (3).
[0091] Under constant temperature of 10℃ for 60 min, the transmitted light intensity fluctuation range of the silk fibroin hydrogel precursor solution was -1.5~3% and the stability index of the silk fibroin hydrogel precursor solution was 1.0.
[0092] The transmission light intensity fluctuation range and stability index of the silk fibroin hydrogel precursor solution prepared in this comparative example are increased compared with those in Example 1. This is because during the preparation process in step (3) of this comparative example, the temperature of the mixed system is always more than 15°C lower than the lower limit of the effective catalytic temperature range of HRP. Under this condition, the thermal motion rate and catalytic activity of HRP molecules are significantly reduced, and it is almost impossible to start an effective enzymatic cross-linking reaction. At this temperature, the viscosity of the silk fibroin hydrogel precursor solution further increases, the molecular diffusion resistance increases, the difficulty of uniform dispersion of H2O2 and enzyme increases, and local molecular entanglement and concentration unevenness cannot be eliminated by diffusion, resulting in a significant increase in the transmission light intensity fluctuation range. The stability index, which integrates the changes in light intensity over the entire height and time, also increases significantly.
[0093] The silk fibroin hydrogel precursor solution used in step (4) was prepared in this comparative example;
[0094] Due to the decreased stability of the silk fibroin hydrogel precursor solution, the silk fibroin molecules aggregated randomly. As a result, the silk fibroin hydrogel prepared with it would clog the needle when used for injection, thus rendering the silk fibroin hydrogel prepared in this comparative example non-injectable.
[0095] Comparative Example 5
[0096] A method for preparing a silk fibroin hydrogel is basically the same as in Example 1, except that in step (2), the mixing is carried out by oscillation only, without alternating oscillation and standing.
[0097] Visible bubbles and gel clumps were generated in the prepared silk fibroin hydrogel precursor solution. Under constant temperature of 10℃ for 60 min, the transmitted light intensity of the silk fibroin hydrogel precursor solution fluctuated within a range of -1.5~1.5% and the stability index of the silk fibroin hydrogel precursor solution was 0.5.
[0098] The transmitted light intensity fluctuation range and stability index of the silk fibroin hydrogel precursor solution prepared in this comparative example increased compared to Example 1. This is because the shear force generated by a single continuous and mild oscillation can only achieve macroscopic mixing and cannot eliminate the local concentration gradient at the microscopic level. H2O2 can only be dispersed at the macroscopic level and cannot penetrate around the entangled regenerated silk fibroin molecular chains through molecular diffusion. In the end, "it looks like it is mixed evenly, but the concentration of oxidant is seriously excessive," which will still cause local gelation. In addition, these gel clumps with a density higher than that of the uncrosslinked silk fibroin solution will undergo continuous and uneven sedimentation under the action of gravity, resulting in a significant increase in the transmitted light intensity fluctuation range. As a result, the stability index, which integrates the changes in light intensity over the entire height and time, also increases significantly.
[0099] The silk fibroin hydrogel precursor solution used in step (4) was prepared in this comparative example;
[0100] Because the silk fibroin hydrogel precursor solution used contained visible gel clumps, the silk fibroin hydrogel prepared with it also caused needle blockage when used for injection. Therefore, the silk fibroin hydrogel prepared in this comparative example is not injectable.
[0101] Comparative Example 6
[0102] A method for preparing silk fibroin hydrogel is basically the same as in Example 1, except that: when adding H2O2 solution in step (3), the method of adding it directly is not used instead of micro-drop addition.
[0103] The prepared silk fibroin hydrogel precursor solution contains nanoscale gel cores;
[0104] The silk fibroin hydrogel precursor solution used in step (4) was prepared in this comparative example;
[0105] Comparing Comparative Example 6 with Example 1, it can be seen that since the silk fibroin hydrogel prepared in this comparative example contains a nanoscale gel core, the nanoscale gel core will be subjected to shear force during the extrusion process, making it easier to generate gel during the extrusion process, which will lead to needle blockage. Therefore, the silk fibroin hydrogel prepared in this comparative example does not have injectability.
[0106] Example 2
[0107] A method for preparing an injectable silk fibroin hydrogel, comprising the following steps:
[0108] (1) Preparation of regenerated silk fibroin solution;
[0109] (1.1) First, put the shredded silkworm cocoons into a soap salt solution (sodium carbonate solution with a molar concentration of 0.06 mol / L) and boil for 40 min to degumme. Repeat the degumming process 3 times. Then, rinse the degummed silk with deionized water 4 times and dry it in an oven at 55℃ for 24 h to produce degummed silk. The degumming bath ratio (silkworm cocoons: soap salt solution) is 1 g: 50 mL.
[0110] (1.2) First, the degummed fibers are dissolved in a 9M lithium bromide solution. Then, the solution obtained after dissolving the degummed fibers in the lithium bromide solution is poured into a dialysis bag. Then, the dialysis bag with a specification of 3500 Da is placed in deionized water to remove ions and small molecules. The mass-to-volume ratio of the degummed fibers to the lithium bromide solution is 1:6, the dissolution temperature is 60℃, and the dissolution time is 7h. The dialysis time is 60h, and the deionized water is replaced every 6h. The volume of deionized water replaced each time is 50 times the volume of the dialysis solution.
[0111] (1.3) After dialysis, the solution was filtered through a PES aqueous filter membrane with a pore size of 0.45 μm and then transferred to a vacuum drying oven. It was concentrated at 55 °C and 20 kPa for 12 h to obtain a regenerated silk fibroin solution.
[0112] The concentration of the regenerated silk fibroin solution was 20 wt%, and the molecular weight of the regenerated silk fibroin was 60 kDa.
[0113] (2) Prepare an HRP solution with a concentration of 800 U / mL by mixing HRP and water;
[0114] (3) Add HRP solution to regenerated silk fibroin solution and stir magnetically at 100 rpm for 2 min to achieve uniform molecular-level dispersion of HRP molecules in silk fibroin system. Then, use a micro-injection pump to add 40 mmol / L H2O2 aqueous solution at a rate of 1.0 mL / min. Then mix in a light-protected environment by alternating shaking and standing to obtain a uniformly dispersed silk fibroin hydrogel precursor solution. During the preparation process, the temperature of the mixing system is always 10℃ lower than the lower limit of the effective catalytic temperature range of HRP. The volume ratio of regenerated silk fibroin solution, HRP solution and H2O2 solution is 10:1.5:0.8. The shaking rate is 120 rpm. The alternating shaking and standing method means: shake for 20 s and stand for 5 min each time, repeat 4 times.
[0115] The viscosity of the uniformly dispersed silk fibroin hydrogel precursor solution was 1600 mPa·s; there were no visible bubbles or gel clumps; under constant temperature of 10℃ for 60 min, the transmitted light intensity of the uniformly dispersed silk fibroin hydrogel precursor solution fluctuated within the range of -0.5~0.5% using a multiple light scattering instrument, and the stability index of the uniformly dispersed silk fibroin hydrogel precursor solution was 0.25.
[0116] (4) The uniformly dispersed silk fibroin hydrogel precursor solution was transferred to a syringe for pre-crosslinking to obtain an injectable silk fibroin hydrogel with a viscosity of 3500 mPa·s; wherein the pre-crosslinking temperature was 22℃ and the pre-crosslinking time was 5 min.
[0117] The gelation time of the final injectable silk fibroin hydrogel was 5 min, the compressive strength after molding was 300 kPa, the compressive modulus was 100 kPa, and the equilibrium swelling rate in PBS was 15%.
[0118] Example 3
[0119] A method for preparing an injectable silk fibroin hydrogel, comprising the following steps:
[0120] (1) Preparation of regenerated silk fibroin solution;
[0121] (1.1) First, put the shredded silkworm cocoons into a soap salt solution (sodium carbonate solution with a molar concentration of 0.1 mol / L) and boil for 60 min to degumme. Repeat the degumming process 3 times. Then, rinse the degummed silk with deionized water 5 times and dry it in an oven at 50℃ for 10 h to make degummed silk. The degumming bath ratio (silkworm cocoons: soap salt solution) is 1 g: 150 mL.
[0122] (1.2) First, dissolve the degummed fibers in a 10M lithium bromide solution. Then, pour the solution obtained after dissolving the degummed fibers in the lithium bromide solution into a dialysis bag. Then, place the dialysis bag with a specification of 3500 Da into deionized water to remove ions and small molecules. The mass-to-volume ratio of the degummed fibers to the lithium bromide solution is 1:10, the dissolution temperature is 80℃, and the dissolution time is 12h. The dialysis time is 48h, and the deionized water is replaced every 12h. The volume of deionized water replaced each time is 100 times the volume of the dialysis solution.
[0123] (1.3) After dialysis, the solution was filtered through a PES aqueous filter membrane with a pore size of 0.45 μm and then transferred to a vacuum drying oven. It was concentrated at 50 °C and 40 kPa for 24 h to obtain a regenerated silk fibroin solution.
[0124] The concentration of the regenerated silk fibroin solution was 8 wt%, and the molecular weight of the regenerated silk fibroin was 60 kDa.
[0125] (2) Prepare an HRP solution with a concentration of 1000 U / mL by mixing HRP and water;
[0126] (3) Add HRP solution to regenerated silk fibroin solution and stir magnetically at 300 rpm for 2 min to achieve uniform molecular-level dispersion of HRP molecules in silk fibroin system. Then, use a micro-injection pump to add 50 mmol / L H2O2 aqueous solution at a rate of 0.1 mL / min. Then mix in a light-protected environment by alternating shaking and standing to obtain a uniformly dispersed silk fibroin hydrogel precursor solution. During the preparation process, the temperature of the mixing system is always maintained at 10℃, the volume ratio of regenerated silk fibroin solution, HRP solution and H2O2 solution is 10:2.5:1.2, the shaking rate is 50 rpm, and the alternating shaking and standing means: shake for 10 s and stand for 8 min each time, and repeat once.
[0127] The viscosity of the uniformly dispersed silk fibroin hydrogel precursor solution was 100 mPa·s; there were no visible bubbles or gel clumps; under constant temperature of 10℃ for 60 min, the transmitted light intensity of the uniformly dispersed silk fibroin hydrogel precursor solution fluctuated within the range of 0.2~0.7% using a multiple light scattering instrument, and the stability index of the uniformly dispersed silk fibroin hydrogel precursor solution was 0.22.
[0128] (4) The uniformly dispersed silk fibroin hydrogel precursor solution was transferred to a syringe for pre-crosslinking to obtain an injectable silk fibroin hydrogel with a viscosity of 1200 mPa·s; wherein the pre-crosslinking temperature was 25℃ and the pre-crosslinking time was 1 min.
[0129] The gelation time of the final injectable silk fibroin hydrogel was 1 min, the compressive strength after molding was 100 kPa, the compressive modulus was 40 kPa, and the equilibrium swelling rate in PBS was 40%.
[0130] Example 4
[0131] A method for preparing an injectable silk fibroin hydrogel, comprising the following steps:
[0132] (1) Preparation of regenerated silk fibroin solution;
[0133] (1.1) First, put the shredded silkworm cocoons into a soap salt solution (sodium carbonate solution with a molar concentration of 0.02 mol / L) and boil for 30 min to degumme. Repeat the degumming process 3 times. Then, rinse the degummed silk with deionized water 3 times and dry it in an oven at 60℃ for 36 h to produce degummed silk. The degumming bath ratio (silkworm cocoons: soap salt solution) is 1 g: 100 mL.
[0134] (1.2) First, the degummed fibers are dissolved in an 8M lithium bromide solution. Then, the solution obtained after dissolving the degummed fibers in the lithium bromide solution is poured into a dialysis bag. Then, the dialysis bag with a specification of 3500 Da is placed in deionized water to remove ions and small molecules. The mass-to-volume ratio of the degummed fibers to the lithium bromide solution is 1:10, the dissolution temperature is 80℃, and the dissolution time is 12h. The dialysis time is 72h, and the deionized water is replaced every 4h. The volume of deionized water replaced each time is 100 times the volume of the dialysis solution.
[0135] (1.3) After dialysis, the solution was filtered through a PES aqueous filter membrane with a pore size of 0.45 μm and then transferred to a vacuum drying oven. It was concentrated at 60 °C and 10 kPa for 14 h to obtain a regenerated silk fibroin solution.
[0136] The concentration of the regenerated silk fibroin solution was 15 wt%, and the molecular weight of the regenerated silk fibroin was 180 kDa.
[0137] (2) Prepare an HRP solution with a concentration of 600 U / mL by mixing HRP and water;
[0138] (3) Add HRP solution to regenerated silk fibroin solution and stir magnetically at 200 rpm for 2 min to achieve uniform molecular-level dispersion of HRP molecules in silk fibroin system. Then, use a micro-injection pump to add 32 mmol / L H2O2 aqueous solution at a rate of 0.3 mL / min. Then mix in a light-protected environment by alternating shaking and standing to obtain a uniformly dispersed silk fibroin hydrogel precursor solution. During the preparation process, the temperature of the mixing system is always maintained at 15℃, the volume ratio of regenerated silk fibroin solution, HRP solution and H2O2 solution is 10:2:1, the shaking rate is 200 rpm, and the alternating shaking and standing method means: shake for 30s and stand for 1 min each time, repeat 8 times.
[0139] The viscosity of the uniformly dispersed silk fibroin hydrogel precursor solution was 2000 mPa·s; there were no visible bubbles or gel clumps; under constant temperature of 10℃ for 60 min, the transmitted light intensity of the uniformly dispersed silk fibroin hydrogel precursor solution fluctuated within the range of -0.3~0.3% using a multiple light scattering instrument, and the stability index of the uniformly dispersed silk fibroin hydrogel precursor solution was 0.21.
[0140] (4) The uniformly dispersed silk fibroin hydrogel precursor solution was transferred to a syringe for pre-crosslinking to obtain an injectable silk fibroin hydrogel with a viscosity of 3000 mPa.s; wherein the pre-crosslinking temperature was 23℃ and the pre-crosslinking time was 3min.
[0141] The gelation time of the final injectable silk fibroin hydrogel was 3 min, the compressive strength after molding was 450 kPa, the compressive modulus was 160 kPa, and the equilibrium swelling rate in PBS was 30%.
[0142] Example 5
[0143] A method for preparing an injectable silk fibroin hydrogel, comprising the following steps:
[0144] (1) Preparation of regenerated silk fibroin solution;
[0145] (1.1) First, put the shredded silkworm cocoons into a soap salt solution (sodium bicarbonate solution with a molar concentration of 0.02 mol / L) and boil for 20 min to degumme. Repeat the degumming process 3 times. Then, rinse the degummed silk with deionized water 3 times and dry it in an oven at 60℃ for 36 h to make degummed silk. The degumming bath ratio (silkworm cocoons: soap salt solution) is 1 g: 100 mL.
[0146] (1.2) First, the degummed fibers are dissolved in an 8M lithium bromide solution. Then, the solution obtained after dissolving the degummed fibers in the lithium bromide solution is poured into a dialysis bag. Then, the dialysis bag with a specification of 3500 Da is placed in deionized water to remove ions and small molecules. The mass-to-volume ratio of the degummed fibers to the lithium bromide solution is 1:3, the dissolution temperature is 40℃, and the dissolution time is 2h. The dialysis time is 72h, and the deionized water is replaced every 4h. The volume of deionized water replaced each time is 100 times the volume of the dialysis solution.
[0147] (1.3) After dialysis, the solution was filtered through a PES aqueous filter membrane with a pore size of 0.45 μm and then transferred to a vacuum drying oven. It was concentrated at 60 °C and 10 kPa for 2 h to obtain a regenerated silk fibroin solution.
[0148] The concentration of the regenerated silk fibroin solution was 8 wt%, and the molecular weight of the regenerated silk fibroin was 250 kDa.
[0149] (2) Prepare an HRP solution with a concentration of 600 U / mL by mixing HRP and water;
[0150] (3) Add HRP solution to regenerated silk fibroin solution and stir magnetically at 200 rpm for 2 min to achieve uniform molecular-level dispersion of HRP molecules in silk fibroin system. Then, use a micro-injection pump to add 32 mmol / L H2O2 aqueous solution at a rate of 0.8 mL / min. Then mix in a light-protected environment by alternating shaking and standing to obtain a uniformly dispersed silk fibroin hydrogel precursor solution. During the preparation process, the temperature of the mixing system is always maintained at 5℃, the volume ratio of regenerated silk fibroin solution, HRP solution and H2O2 solution is 10:2:1, the shaking rate is 150 rpm, and the alternating shaking and standing method means: shake for 30s and stand for 1 min each time, repeat 8 times.
[0151] The viscosity of the uniformly dispersed silk fibroin hydrogel precursor solution was 1500 mPa·s; there were no visible bubbles or gel clumps; under constant temperature of 10℃ for 60 min, the transmitted light intensity of the uniformly dispersed silk fibroin hydrogel precursor solution fluctuated within the range of -1 to 1% using a multiple light scattering instrument, and the stability index of the uniformly dispersed silk fibroin hydrogel precursor solution was 0.28.
[0152] (4) The uniformly dispersed silk fibroin hydrogel precursor solution was transferred to a syringe for pre-crosslinking to obtain an injectable silk fibroin hydrogel with a viscosity of 2500 mPa.s; wherein the pre-crosslinking temperature was 23℃ and the pre-crosslinking time was 4min.
[0153] The gelation time of the final injectable silk fibroin hydrogel was 2 min, the compressive strength after molding was 300 kPa, the compressive modulus was 150 kPa, and the equilibrium swelling rate in PBS was 16%.
Claims
1. A method for preparing an injectable silk fibroin hydrogel, characterized in that: Horseradish peroxidase solution was added to regenerated silk fibroin solution and stirred evenly. Then, H2O2 solution was added dropwise. The mixture was then mixed in a light-protected environment by alternating between shaking and standing to obtain a uniformly dispersed silk fibroin hydrogel precursor solution. Finally, the uniformly dispersed silk fibroin hydrogel precursor solution was transferred to a syringe for pre-crosslinking to obtain injectable silk fibroin hydrogel. Micro-dropleting refers to adding H2O2 solution dropwise at a rate of 0.1~1.0 mL / min using a micro-injection pump; During the preparation of the uniformly dispersed silk fibroin hydrogel precursor solution, the temperature of the mixing system was maintained within the range of 5~15℃. The concentration of the regenerated silk fibroin solution is 8~20wt%, and the molecular weight of the regenerated silk fibroin is 60~250kDa; The oscillation rate is 50~200 rpm; The gelation time of injectable silk fibroin hydrogel is 1~5 min, the compressive strength after molding is 100~450 kPa, the compressive modulus is 40~160 kPa, and the equilibrium swelling rate in PBS is 15~40%.
2. The method for preparing an injectable silk fibroin hydrogel according to claim 1, characterized in that, The concentration of horseradish peroxidase solution is 600~1000 U / mL, and the concentration of H2O2 solution is 32~50 mmol / L; The volume ratio of regenerated silk fibroin solution, horseradish peroxidase solution, and H2O2 solution is 10:1.5~2.5:0.8~1.
2.
3. The method for preparing an injectable silk fibroin hydrogel according to claim 1, characterized in that, The alternation of oscillation and rest refers to: oscillation for 10-30 seconds each time, rest for 1-8 minutes, and repeating 1-8 times.
4. The method for preparing an injectable silk fibroin hydrogel according to claim 1, characterized in that, The viscosity of the uniformly dispersed silk fibroin hydrogel precursor solution is 100~2000 mPa·s; there are no visible bubbles or gel clumps; under constant temperature of 10℃ for 60 min, the transmitted light intensity of the uniformly dispersed silk fibroin hydrogel precursor solution fluctuates within the range of -1.0~1.0% using a multiple light scattering instrument, and the stability index of the uniformly dispersed silk fibroin hydrogel precursor solution is <0.
3.
5. The method for preparing an injectable silk fibroin hydrogel according to claim 1, characterized in that, The pre-crosslinking temperature is 20~25℃, the pre-crosslinking time is 1~10min, and the viscosity of the injectable silk fibroin hydrogel is 1200~3500 mPa.s.
6. The method for preparing an injectable silk fibroin hydrogel according to claim 1, characterized in that, The preparation method of regenerated silk fibroin solution is as follows: silkworm cocoons are immersed in soap salt solution for degumming, washing and drying to produce degummed silk; Degummed silk fibers are dissolved in lithium bromide solution, dialyzed to desalt, and concentrated to produce a regenerated silk fibroin solution.
7. The method for preparing an injectable silk fibroin hydrogel according to claim 6, characterized in that, The soap salt solution is a sodium carbonate solution or sodium bicarbonate solution with a molar concentration of 0.02~0.1 mol / L.
8. The method for preparing an injectable silk fibroin hydrogel according to claim 6, characterized in that, The mass-to-volume ratio of degummed fibers to lithium bromide solution is 1:3~10; the concentration of lithium bromide solution is 8~10M; the dissolution temperature is 40~80℃; and the dissolution time is 2~12h.
Citation Information
Patent Citations
Preparation method of injectable functional fibroin-based hydrogel
CN121796644A
Method for preparing silk fibroin hydrogel based on double-enzyme sequential catalytic system
CN122483358A